How Cartoon Can Improve Speaking Skill - Jaisy Yasmin Alphariyadi; Lusiana Suciati Dewi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to look at the effectiveness of cartoon based learning to improve speaking skills. Researchers used a qualitative method. The subject was a Junior High Schooler student (SMP). Research results will show the effectiveness of cartoon base learning from observation and interviews. Cartoons were rated for their effectiveness on improving learning outcomes. The findings and presentation skills improved and their confidence to speak in front of the class increased, students also learned technology which is beneficial for their study and future career. Therefore, suggests that teachers consider this aid in theaching-learning processes.